Per Jacobsson Lecture : What Financial System for the Twenty-First Century?. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper describes a financial system that should be adopted for the 21st century. The paper highlights that the financial crisis of 2008 has raised fundamental questions about how the financial industry is structured, managed, and regulated. The paper discusses that a well-functioning financial system plays an essential role in generating high levels of saving, promoting the efficient allocation of investment, and smoothing economic fluctuations stemming from nonfinancial causes. By facilitating informed risk taking, it is a key element in achieving optimal levels of productivity growth and rising living standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet